Processability and mechanical properties of spent coffee ground (SCG) and polypropylene biocomposites (2024)
The circular economy encourages optimizing use of plastics, waste reduction, sustainable materials, and processing of plastic products. In this framework, the use of agricultural waste materials promotes waste reduction and eco-design in plastic product manufacturing. This study researched the preparation of an isotatic polypropylene (PP) matrix (MFI 50 grade) with spent coffee grounds (SCG) and various commercial additives. The biocomposites were analyzed to evaluate their mechanical properties and processability. PP and SCG composites were synthesized with 30% SCG content with maleic anhydride grafted polypropylene (PP-g-MA), stearic acid and epoxidized oil as compatibilizers. The study found that polypropylene grafted with maleic anhydride (PP-g-MA) as a compatibilizer improves SCG dispersion, enhancing processing stability. Epoxidized oil (EO) and stearic acid (SA) can also function as lubricants that significantly improve composite processability by decreasing specific energy and shear viscosity. The processability properties were accessed using a torque rheometer. A tensile test showed that while SCG addition decreases mechanical strength, PP-g-MA improves interfacial adhesion, and EO and SA increase flexibility by reducing brittleness.